Entidades de apoio e comunidades quilombolas análise sobre o circuito quilombola de turismo comunitário do Vale do Ribeira - Pires, João Henrique Souza (Editora Oficina Universitária, 2022)
In this book, the result of a broad bibliographical and documental survey, and relevant empirical research for understanding the object of study, João Henrique Souza Pires seeks to analyze the impact of the activities of Support Entities that develop work related to training, education, advice, technical assistance and extension in the organization of tourism in Quilombola Communities of Vale do Ribeira, in the state of São Paulo. The author focuses on theoretical and methodological issues that guide the work of these entities in quilombola territories, demonstrating, through the discussion of the results of his extraordinary research, that the activities developed there are guided by a critical, horizontal, dialogical, problematizing logic and exchange of knowledge with traditional peoples who develop the Quilombola Circuit of Community Tourism of Vale do Ribeira. In this way, it is a fundamental work for those who seek to know the resistance and historical struggle of the quilombolas for the recognition of their territories and preservation of their way of life. In addition, the author points out that the training practices of technical assistance developed there, by contemplating tourism aimed at valuing the territory and the self-organization of quilombola subjects, enhance the resistance process of these communities and oppose the systematic advance of agribusiness sectors , real estate speculation and mining in quilombola areas, sectors regulated by capitalist logic and destroyers of traditional cultures. João Pires, thus, lays bare to the reader the historical evidence of the quilombolas as a "class in itself" in the context of the struggles undertaken in the Ribeira Valley.